Penerapan Desain Eksperimen Dalam OPtimasi Formula Mikroemulsi Tea Tree Oil - Nugraheni, Raditya Weka; Chasanah, Uswatun (Universitas Muhammadiyah Gresik, 2019)
Microemulsion is a transparent, isotropic and thermodynamically stable preparation. Tea tree oil (TTO) is an essential oil extracted from the leaves of Melaleuca alternifolia by steam distillation which has been proven to have antibacterial and fungal uses. Optimization of microemulsion preparations to obtain preparations with small and stable droplet size is also a challenge. The design of an experiment is to design an experiment with a certain pattern, with a combination of certain input variables that allow to shorten the number of experiments. Based on the research results, it is known that the most influential factor on the microemulsion particle size is the combination of surfactants polysorbate 80 with co-surfactants propyleneglycol.